Shared Cell Biological Functions May Underlie Pleiotropy of Molecular Interactions in the Germ Lines and Nervous Systems of Animals - Kulkarni, Arpita; Lopez, Davys H.; Extavour, Cassandra G. (Frontiers in Ecology and Evolution, 2020)
Evolutionary developmental biology focuses on understanding the origin and evolution of extant biological variation, and the genetic basis for this variation. The genetic toolkit appears largely finite across animals, such that a combination of regulatory evolution, gene recruitment (co-option) and genetic modularity often allow morphological and developmental diversity to arise. Here we summarize a number of observations from across animals, which together suggest that many genes and gene product interaction “modules” originally characterized for their role in the germ line also have neural roles. We explore potential explanations for this observation, noting that in the context of the germ line, these genes appear to have molecular and biochemical properties that make them well-suited to breaking symmetry within cells. The resulting asymmetry is often caused by gene products co-localizing asymmetrically to sub-cellular, non-membrane-bound, electron dense compartments known as ribonucleoprotein (RNP) granules. RNP granules contain high concentrations of translationally quiescent messenger RNAs and proteins and are thought to act as hubs of localized translational control. We propose that the use of strict translational control, which may be achieved molecular processes important for RNP granule formation and/or small RNA-related processes, is an important property of and a commonality between the germ line and nervous tissues, and help explain, at least in part, the close relationship between these two tissue types.